Effect of post space preparation drills on the incidence of root dentin defects - Thaíse Ayres Bezerra Zuli; Orlando Aguirre Guedes; Gislaine Figueiredo Zarza Arguello Gonçalves; Aurélio Rosa da Silva Júnior; Álvaro Henrique Borges; Andreza Maria Fábio Aranha (Restorative Dentistry & Endodontics)
ObjectivesThis study investigated the incidence of root dentin defects after the use of different post space preparation (PSP) drills.Materials and MethodsSeventy-two bovine incisors were selected and obtained 14-mm-long root sections. Twelve roots served as controls with no intervention (G1). The 60 root canals remaining were instrumented using the crown-down technique with the ProTaper Next system and obturated using the lateral condensation technique. Specimens were randomly distributed into 5 groups (n = 12) according to the operative steps performed: G2, root canal instrumentation and filling (I+F); G3, I+F and PSP with Gates-Glidden drills; G4, I+F and PSP with Largo-Peeso reamers; G5, I+F and PSP with Exacto drill; and G6, I+F and PSP with WhitePost drill. Roots were sectioned at 3, 6, 9, and 12 mm from the apex, and digital images were captured. The presence of root dentin defects was recorded. Data were analyzed by the χ2 test, with p < 0.05 considered to indicate statistical significance.ResultsRoot dentin defects were observed in 39.6% of the root sections. No defects were observed in G1. G5 had significantly more cracks and craze lines than G1, G2, and G3 (p < 0.05), and more fractures than G1, G2, G3, and G4 (p < 0.05). When all root sections were analyzed together, significantly more defects were observed at the 12-mm level than at the 3-mm level (p < 0.05).ConclusionsPSP drills caused defects in the root dentin. Gates-Glidden drills caused fewer root defects than Largo-Peeso reamers and Exacto drills.